Post-genome informatics - Kanehisa, Minoru (Oxford University Press, 2000)
The genome projects have now entered a rapid production phase with complete genome sequences and complete gene catalogues already available for a number of organisms and an increasing number expected shortly. In addition the new DNA and protein chip technologies can produce functional data about genes such as gene expression profiles at a rapid rate. There is therefore a large and ever increasing amount of data about genes and molecules...